The impact of prenatally diagnosed Klinefelter Syndrome on obstetric and neonatal outcomes. (August 2016) - Dotters-katz, Sarah K; Humphrey, Whitney M.; Senz, Kayli L.; Lee, Vanessa R.; Shaffer, Brian L.; Caughey, Aaron B.
Abstract: Objective: The objective of this study was to examine the obstetric and neonatal outcomes as well as the as the associated hospital costs for pregnancies complicated by prenatally diagnosed Klinefelter Syndrome, 47, XXY. Study design: We conducted a retrospective cohort study of all of the singleton deliveries in California from 2005 to 2008 using vital statistics and ICD-9 data, specifically identifying cases of fetal Klinefelter Syndrome. Specifically, we were interested in the outcomes of preterm delivery, preeclampsia, intrauterine fetal demise, cesarean delivery, neonatal death, respiratory distress syndrome (RDS), small for gestational age, large for gestational age, neonatal death, and infant death. Bivariate and multivariate analyses were used to compare pregnancies and neonates affected by prenatally diagnosed Klinefelter Syndrome to those that were not affected with 47, XXY. Results: There were 2, 029, 000 deliveries in the cohort, including 52 women with prenatally diagnosed 47, XXY. Advanced maternal age, completion of 12th grade, and private insurance were all associated with a prenatal diagnosis of Klinefelter Syndrome. Compared to unaffected deliveries, pregnancies complicated by prenatally diagnosed Klinefelter Syndrome had higher rates of preterm delivery (23.1% vs 9.9%, p = 0.0004), cesarean delivery (50.0% vs 30.2%, p = 0.004), and RDS (9.6% vs 1.2%, p = <0.0001). Infants with 47, XXY were markedly more likely to be small for gestational age, including less than the 10th, 5th and 3rd percentile (aOR 5.86 (95% CI 2.99, 11.46), 6.03 (95% CI 2.52, 14.43), and 8.28 (95% CI 3.22, 21.25), p ≤ 0.001). Rates of neonatal death were 9.5 times higher (1.9% vs 0.2% p < 0.0001) in the 47, XXY cohort, and rates of infant death were more than 50 times higher (5.8% vs 0.1%, p < 0.0001). In the adjusted analysis, prenatally diagnosed 47, XXY was associated with increased odds of preterm delivery <32 weeks (OR 6.81, 95% CI 2. .38, 19.52), IVH (OR 9.08, 95% CI 1.22, 67.7), RDS (OR 8.32, 95% CI 3.22, 21.49), neonatal death (OR 9.77, 1.33, 71.79), and infant death (OR 62.73, 95% CI 19.34, 203.4). Conclusion: Pregnancies affected by prenatally diagnosed Klinefelter Syndrome are at an increased risk of adverse fetal and neonatal outcomes. These findings may be helpful when counseling families with pregnancies affected by fetal 47, XXY.